Гомоцистеїн як чинник кардіоваскулярного ризику у хворих на гіпотиреоз - Михайленко, О. Ю.; Зубкова, С. Т. (Clinical Endocrinology and Endocrine Surgery, 2013)
Homocysteine level was investigated in plasma of patients with hypothyroidism and its changes were analyzed depending on the levels of TSH, total cholesterol, BMI, values of arterial pressure. The presence of its increase by 11-13% against the background of the disease decompensation, increased levels of arterial blood pressure, total cholesterol, BMI were revealed in patients aged 60-73 years. The deformation of the carotid arteries was observed in the most part of the examined patients and atherosclerotic plaques, unsignificant hemodynamically, with homocysteine levels in the range of 6-19 mkmol/l were noted nearly in half of them. Hyperhomocysteinemia was accompanied by an increase in the diameter of the common carotid artery.